Having a Family Doctor is Associated with Some Better Patient-Reported Outcomes of Primary Care Consultations - Lam, Cindy L. K.; Yu, Esther Y. T.; Lo, Yvonne Y. C.; Wong, Carlos K. H.; Mercer, Stewart M.; Fong, Daniel Y. T.; Lee, Albert; Lam, Tai Pong; Leung, Gabriel M. (Frontiers in Medicine, 2014)
Background: Hong Kong (HK) has pluralistic primary care that is provided by a variety of doctors. The aim of our study was to assess patient-reported outcomes of primary care consultations in HK and whether having a family doctor made any difference. Methods: We interviewed by telephone 3148 subjects from 5174 contacted households (response rate 60.8%) randomly selected from the general population of HK about the experience of their last primary care consultations in September 2007 and April 2008. We compared the patient reported outcomes (PRO) and patient-centred process of care in those with a family doctor (FD), those with other types of regular primary care doctors (ORD) and those without any regular primary care doctor (NRD). PRO included patient enablement, global improvement in health, overall satisfaction and likelihood of recommending their doctors to family and friends. Patient-centred process of care indicators were explanations about the illness, and address of patient’s concerns. Results: 1150, 746 and 1157 reported to have FD, ORD and NRD, respectively. Over 80% of those with FD consulted their usual primary care doctors in the last consultation compared with 27% of those with NRD. Compared with subjects having ORD or NRD, subjects with FD reported being more enabled after the consultation and were more likely to recommend their doctors to family and friends. Subjects with FD and ORD were more likely than those having NRD to report a global improvement in health and satisfaction. FD group was more likely than the other two groups to report receiving an explanation on the diagnosis, nature and expected course of the illness, and having their concerns addressed. Patient enablement was associated with explanation of diagnosis,nature and expected course of the illness and address of patient’s concerns. Conclusions: People with a regular family doctor were more likely to feel being enabled and to experience patient-centred care in consultations.